Technology and Nursing - Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
In the present age we cannot disassociate from emerging issues, which involve science, communication, health and technology, the influence of media, technological advances, and the use of computers in all spheres of life. The concepts created for technology cover various evaluation approaches, which depend upon which type of technology, approaches, usefulness and influences in a particular area of knowledge. Technological advances cover several areas, figuring quantum physics, nanotechnology, astronomy, computer science, medicine, nursing, psychology, etc.